2019
DOI: 10.1038/s41598-019-53544-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of reference genes for gene expression analysis by real-time quantitative PCR (qPCR) in three stingless bee species (Hymenoptera: Apidae: Meliponini)

Abstract: Stingless bees are generalist pollinators distributed through the pantropical region. There is growing evidence that their wild populations are experiencing substantial decline in response to habitat degradation and pesticides. Policies for conservation of endangered species will benefit from studies focusing on genetic and molecular aspects of their development and behavior. The most common method for looking at gene expression is real-time quantitative polymerase chain reaction preceded by reverse transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 69 publications
0
24
0
3
Order By: Relevance
“…Previous studies have shown that some ribosome-associated genes have been used as stable internal reference genes for quantitative analysis ( Wang et al, 2019 ). For instance, Freitas et al (2019) found that rpl 32, rps 5, and rps 18 were identified as suitable reference genes for the different tissues of stingless bees. Similarly, rpl23 was identified the reliable reference gene in bumblebees challenged by IAPV ( Niu et al, 2014 ; Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that some ribosome-associated genes have been used as stable internal reference genes for quantitative analysis ( Wang et al, 2019 ). For instance, Freitas et al (2019) found that rpl 32, rps 5, and rps 18 were identified as suitable reference genes for the different tissues of stingless bees. Similarly, rpl23 was identified the reliable reference gene in bumblebees challenged by IAPV ( Niu et al, 2014 ; Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Primers based on each respective gene sequence were designed with Primer3 from Geneious R11 [20] (electronic supplementary material, table S1). Actin ( act ) and 40S ribosomal protein S5 ( rps5 ) were used as references for gene expression normalization [2123]. StepOnePlus Real-Time PCR System (Applied Biosystems, USA) was used for the RT-qPCR assays, and primer amplification efficiency was calculated with qBASE+ software [24] from the slope of a five-point 1:10 serial dilution of calibrator cDNA samples.…”
Section: Methodsmentioning
confidence: 99%
“…The commonality and discrepancies displayed here confirm the notion that no universal reference genes exist for all contexts and reference gene selection and validation is crucial for accurate quantification of gene expression under specific experimental conditions. Without these studies, single un-validated endogenous controls can have profound impacts on data analysis and lead to questionable interpretation 16,18,19,45,46 . In this study, the expression of Hex-1 was significantly underestimated in the 1st nymphs when the least stable instead of the most stable and recommended reference genes was used to normalize target gene expression.…”
Section: Stability Assessmentmentioning
confidence: 99%